PERITONEAL TUBERCULOSIS IN YOUNG AGE LADY MIMICKING GYNECOLOGY MALIGNANCY : A CASE REPORT - Lusi Jelita Sari; Puja Agung Antonius; Syamel Muhammad (Andalas Obstetrics And Gynecology Journal, 2024)
Background : Peritoneal tuberculosis is one of the most challenging forms of extrapulmonarytuberculosis to diagnose. Extrapulmonary TB is very difficult to diagnose because of its non-specific signs and symptoms, thus it sometimes leads to a diagnosis of gynaecologicalmalignancy such as advanced ovarian carcinoma.Case Report : A teenage girl, 12 years old, with a chief complaint of intermittent abdominalpain since the last 1 month. There was no history of an enlarged abdomen, fever and weightloss. Ultrasound examination revealed an irregular adnexal mass suggesting an ovarianmalignancy with other possibilities of an infectious process. Diagnostic laparoscopy andperitoneal biopsy were performed on the patient. Intraoperatively, multiple friable nodular-mylar peritoneal masses with abdominopelvic attachments and fibrin fibres and white vesicleswere found on the entire surface of the genitalia, peritoneum, and intestines. A mass biopsywas performed with histopathological results showing peritoneal tuberculosis. Currently, thepatient is undergoing anti-tuberculosis drugs (OAT) treatment.Discussion : The diagnosis of this disease is difficult to establish. Symptoms are highlyvariable and non-specific and can lead to the wrong tumour pathology. The clinicalcharacteristics are dominated by changes in general condition, abdominal pain and transitdisorders, as well as masses (20 to 25%). The gold standard for definitive PTB diagnosisremains laparoscopy with peritoneal biopsy and subsequent pathological or microbiologicalconfirmation. Yellow/white nodules in the peritoneum observed on the patient's laparoscopicimages are the hallmark of wet peritoneal TB. Omental thickening and abdominal cocoon withmatted small bowel are other classic laparoscopic findings for peritoneal TB.Conclusion : PTB has similar characteristics to peritoneal carcinoma, which makes diagnosisdifficult for clinicians. Early and correct diagnosis of PTB helps to initiate medical managementquickly and helps reduce morbidity and mortality.